Hadith #1109 - Sunan Ibn Majah - Abu al-Darda; Asim bin Rja'a bin Hywh عاصم بن رجاء بن حيوة الكندي الفلسطيني; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sulaiman bin 'Abdur Rahman سليمان بن عبد الرحمن بن عيسى; Uthman bin Fa'id al-Quraishi عثمان بن فائد القرشي أبو لبابة البصري (Sunan Ibn Majah)
“A group from the people of ‘Iraq came to ‘Umar and when they came to him, he said to them: ‘Where are you from?’ They said: ‘From the inhabitants of ‘Iraq.’ He said: ‘Have you come with permission?’ They said: ‘Yes.’ Then they asked him about a man’s prayer in his house. ‘Umar said: ‘I asked the Messenger of Allah (ﷺ) and he said: “As for a man’s prayer in his house, it is light, so illuminate your houses.’”” Another chain with similar wording.
Grade: